ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Suryanti, Desy; Sari, Lita Permata; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The purpose of this study was to determine the effect of liquidity and leverage on the firm value with profitability as an intervening variable in food and beverage companies listed on the Indonesian stock exchange for the 2019-2021 period. The population of this study is all food and beverage companies listed on the IDX, totaling 30 companies. The sampling technique in this study used purposing sampling so that 12 samples of data analysis were obtained. Data analysis and hypothesis testing in this study used Smart PLS 3.0 application. The results of this study indicated that Liquidity had a positive significant effect on Profitability, Leverage had a negative significant effect on Profitability, Liquidity had a negatife significant effect on Firm Value, Leverage and Profitability had a positive significant effect on Firm Value, Liquidity had a positive significant effect on Firm Value through Profitability and Leverage had a negative significant effect on Firm Value through Profitability.